2014
DOI: 10.1093/annhyg/meu068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Welding Fume on Systemic Iron Status

Abstract: Iron is the major metal found in welding fumes, and although it is an essential trace element, its overload causes toxicity due to Fenton reactions. To avoid oxidative damage, excess iron is bound to ferritin, and as a result, serum ferritin (SF) is a recognized biomarker for iron stores, with high concentrations linked to inflammation and potentially also cancer. However, little is known about iron overload in welders. Within this study, we assessed the iron status and quantitative associations between airbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…In brief, hemoglobin (Hb) was measured with a STKR hematology analyzer (Beckman Coulter, Krefeld, Germany) and serum ferritin (SF), using the BN II nephelometer (Siemens Healthcare, Eschborn, Germany). We considered the Fe status as low if Hb < 13 g dl −1 and high if SF ≥ 400 µg l −1 (Casjens et al, 2014). Gamma-glutamyl transferase (GGT) was determined with the ADVIA 1650 chemistry analyzer (Siemens Healthcare).…”
Section: Markers Of Fe Status and Liver Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, hemoglobin (Hb) was measured with a STKR hematology analyzer (Beckman Coulter, Krefeld, Germany) and serum ferritin (SF), using the BN II nephelometer (Siemens Healthcare, Eschborn, Germany). We considered the Fe status as low if Hb < 13 g dl −1 and high if SF ≥ 400 µg l −1 (Casjens et al, 2014). Gamma-glutamyl transferase (GGT) was determined with the ADVIA 1650 chemistry analyzer (Siemens Healthcare).…”
Section: Markers Of Fe Status and Liver Dysfunctionmentioning
confidence: 99%
“…This tight regulation is reflected in a weak correlation between the systemic burden with Mn and Fe and with the parent metal concentration in welding fumes (Pesch et al, 2012). Occupational exposure to metal fumes may cause dyshomeostasis in the systemic concentrations of both these metals, also liver dysfunction contributes to elevated blood levels (Rovira et al, 2008;Pesch et al, 2012;Casjens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, here we did not examine the eating habits and the taking of industrially derived foods, which may similarly contain traces of toxicants or abnormal concentrations of metals and minerals. However, since both the environmental pollution and nutrition can modify physiological body levels of metals [ 16 , 20 23 ], we measured serum concentration of iron, copper, mercury, and manganese as indexes of environmental toxicants exposure, but we did not find significant differences between PD and controls.…”
Section: Discussionmentioning
confidence: 95%
“…Compelling evidence demonstrated the role of iron, copper, manganese, and mercury in the pathogenesis of PD [ 12 17 ] and a number of studies showed abnormal metal serum levels in PD patients [ 18 , 19 ]. Since both the environmental pollution and the eating habits may affect the metal concentrations [ 16 , 20 23 ], such levels could be measured as an index of toxicants exposure. Here we explored serum levels of iron, copper, manganese, and mercury aimed at identifying further elements supporting the PD-risk stratification.…”
Section: Methodsmentioning
confidence: 99%
“…Airborne iron may be responsible for siderosis and lung cancer among welders [74, 75], and periodical quantitative assessment of serum ferritin (SF) has been proposed as a reasonable exposure biomarker in welders using high-emission technologies of respirable iron [76]. Evaluation of SF and serum transferrin levels has been also successfully applied in diagnosing methylene-di-isocyanate OA with a specificity of 85.7% [70] but not in toluene-di-isocyanate OA [77].…”
Section: Assessment Of Biomarkers In Skin and Blood Samplesmentioning
confidence: 99%